1997
DOI: 10.1007/s002449900199
|View full text |Cite
|
Sign up to set email alerts
|

Psyllids as a Potential Source of Heavy Metals for Predators

Abstract: Covariance analysis of fluctuations in local populations of pear psyllids and anthocorid bugs Scutereanu, P.; Lingeman, R.; Drukker, B.; Sabelis, M.W. Abstract. 1. To test whether predatory anthocorids migrate into pear orchards when populations of pear psyllids are building up, a cross-correlation analysis was carried out on their population numbers. Predator and prey population sizes were assessed weekly in 3 consecutive years (1991±93) by sampling pear leaves for eggs and nymphs of psyllids and pear tree br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Concentrations of Cd and Zn in pea shoots were higher than those found in wheat shoots grown earlier in the crop rotation in the same plots, but the concentrations of both metals were lower in the pea aphids than in the grain aphids ( Sitobion avenae ) feeding on the wheat crop . In the Psyllidae (jumping plant lice), the concentration of trace metals has been reported to vary significantly among different species, even among those feeding on the same plant species . Psyllidae are phloem-feeding insects in the same suborder as aphids (the Sternorrhyncha).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Concentrations of Cd and Zn in pea shoots were higher than those found in wheat shoots grown earlier in the crop rotation in the same plots, but the concentrations of both metals were lower in the pea aphids than in the grain aphids ( Sitobion avenae ) feeding on the wheat crop . In the Psyllidae (jumping plant lice), the concentration of trace metals has been reported to vary significantly among different species, even among those feeding on the same plant species . Psyllidae are phloem-feeding insects in the same suborder as aphids (the Sternorrhyncha).…”
Section: Discussionmentioning
confidence: 94%
“…Aphids are generally specialist herbivores and therefore different species of aphids are found on different crops. The efficiency of trace metal regulating physiology within arthropods is species specific and can vary significantly, even between closely related species , . Thus, the trace metal accumulation characteristics of the crop plant and its associated aphid species may combine to have an antagonistic or synergistic effect on the transfer of trace metal from the soil to the predator trophic level.…”
Section: Introductionmentioning
confidence: 99%
“… Ropek and Para (2002) showed that copper fungicides inhibit the growth and infectivity of Verticillium lecanii , an entomopathic fungus that can be important for aphid control in citrus ( Rondon et al ., 1981 ; Michaud, 1999 ). Glowacka et al . (1997) studied heavy metal loads in 14 species of psyllids (Homoptera: Psyllidae) from polluted regions in Finland and found that wax and honeydew secretions were major routes of copper elimination that largely prevented significant bioaccumulation in these insects.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the phylum Arthropoda consists of a diverse range of organisms, which is reflected in the diversity of trace metal concentrations found in the species of this phylum (Dar et al, 2019). This is the case among even closely related species feeding on similar diets and is derived from inter-specific differences in physiology (Glowacka et al, 1997;Janssen et al, 1991;Laskowski and Maryanski, 1993;Rabitsch, 1995;Sá et al, 2008), which results in some species exhibiting a poor ability to regulate internal trace metal concentrations (Dallinger, 1993;Janssen et al, 1991;Kramarz, 1999b). This section examines the physiology of arthropods that affects the transfer and accumulation of trace metals from their food.…”
Section: Invertebrate Herbivoresmentioning
confidence: 99%